Perturbations in the Urinary Exosome in Transplant Rejection - Sigdel, Tara K.; Ng, Yolanda W.; Lee, Sangho; Nicora, Carrie D.; Qian, Wei-Jun; Smith, Richard D.; Camp, David G.; Sarwal, Minnie M. (Frontiers in Medicine, 2015)
Urine exosomes are small vesicles exocytosed into the urine by all renal epithelial cell types under normal physiologic and disease states. Urine exosomal proteins may mirror disease specific proteome perturbations in kidney injury. Analysis methodologies for the exosomal fraction of the urinary proteome were developed for comparing the urinary exosomal fraction versus unfractionated proteome for biomarker discovery. Urine exosomes were isolated by centrifugal filtration of urine samples collected from kidney transplant patients with and without acute rejection, which were biopsy matched. The proteomes of unfractionated whole urine (Uw) and urine exosomes (Ue) underwent mass spectroscopy-based quantitative proteonomics analysis. The proteome data were analyzed for significant differential protein abundances in acute rejection (AR). A total of 1018 proteins were identified in Uw and 349 proteins in Ue. 279 overlapped between the two urinary compartments and 70 proteins were unique to the Ue compartment. Of 349 exosomal proteins identified from transplant patients,220 had not been previously identified in the normal Ue fraction. 11 Ue proteins, functionally involved in an inflammatory and stress response, were more abundant in urine samples from patients with acute rejection, 3 of which are exclusive to the Ue fraction. Ue AR-specific biomarkers(8) were also detected in Uw, but since they were observed at significantly lower abundances in Uw, they were not significant for AR in Uw. A rapid urinary exosome isolation method and quantitative measurement of enriched Ue proteins was applied. Perturbed proteins in the exosomal compartment of urine collected from kidney transplant patients were specific to inflammatory responses, and were not observed in the Ue fraction from normal healthy subjects. Ue specific protein alterations in renal disease provide potential mechanistic insights and offer a unique panel of sensitive biomarkers for monitoring AR.